2015
DOI: 10.22146/jpki.25263
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Profesionalisme Kedokteran dalam Persepsi Instruktur dan Mahasiswa

Abstract: Background: Profesionalism has become a main competency for physician. Therefore, it is important to get an agreement from health provider about professionalism and it’s applicable learning method for medical institution. This research aimed to explore skills laboratory instructor and student’s perception of the learning method that can facilitate the mastery of professionalism and it’s professional behavior components.Method: A descriptive qualitative method was carried out in this research. Data was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
0
3
0
7
Order By: Relevance
“…Implementation and assessment of professionalism in medical education is yet very basic. This is proven in previous research that found only some institutions integrated professionalism in their curriculum [3].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Implementation and assessment of professionalism in medical education is yet very basic. This is proven in previous research that found only some institutions integrated professionalism in their curriculum [3].…”
Section: Introductionmentioning
confidence: 77%
“…Medical and health professionals have agreed on professionalism. However, according to Cruess [1], the majority of components of professionalism are implicit understanding. For instance, professionalism is a competency mapped into doctor competency standard [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Profesionalisme dalam kedokteran juga dibentuk dari beberapa komponen perilaku, antara lain altruisme, kompetensi, kejujuran, dan menghormati orang lain. 3 CDK-291/ vol. 47 no.…”
Section: Latar Belakangunclassified
“…2020 Konsep profesionalisme dalam institusi pendidikan kedokteran belum dapat dikembangkan dengan baik dalam kurikulum pendidikan sebagai sebuah metode pengajaran dan pembelajaran serta penilaian profesionalisme. 3 Hal ini dapat disebabkan karena belum ada kesepakatan definisi profesionalisme dan komponenkomponennya. 3 Fakultas Kedokteran Universitas Tanjungpura sebagai institusi pendidikan kedokteran di Provinsi Kalimantan Barat, merupakan institusi yang terus berkembang, pembelajaran konsep profesionalisme masih menjadi kendala yang harus diselesaikan.…”
Section: Latar Belakangunclassified